Response of Anastrepha fraterculus Wiedemann (Diptera:Tephritidae) to synthetic semiochemicals - Carrizo, Beatriz Noemi; Ruiz, Josefina; Goane, Lucía; Bachmann, Guillermo Enrique; Milla, Fabian Horacio; Segura, Diego Fernando; Kuzmich, Dan; Walse, Spencer; Vera, María (Estación Experimental Agropecuaria Famaillá, INTA, 2024)
Póster